Sosial Mapping Pengembangan Rencana Induk Program Pemberdayaan Masyarakat (PPM) Perusahan Lingkar Tambang di Kecamatan Kabaena Selatan - Sakti, Putra; H, Haydir (Yayasan Daarul Huda Kruengmane, 2024)
South Kabaena District is one of the distribution areas of Nickel Mining Business Permits, until now the company is still carrying out Nickel Laterite Production and Sales operations. The presence of the company in South Kabaena District certainly affects the level of community activity in the fields of agriculture and fishing, so the PPM program can help reduce the social impacts caused by the mining community. The Community Development and Empowerment Master Plan (PPM) is an activity that is directed at increasing community access to achieve better social, economic and cultural conditions when compared to before there were Mining activities around the community's living environment.